A dynamic detection method based on Web crawler and page code behavior for XSS vulnerability - Yi LIU; Junbin HONG (Dianxin kexue)
XSS vulnerability is a common vulnerability of attacking the Web application and getting the user’s privacy data.Traditional XSS vulnerability detection’s softwares aren’t specially detecting for AJAX Web application.There is a huge disparity in the inspection accuracy.According to this situation，the XSS vulnerability characteristics of AJAX Web applications were described in detail，and a dynamic detection method based on Web crawler and page code behavior was proposed.Experimental results show that the proposed method has good performance in labor-saving，time saving and vulnerability detection effect.